Optimizing Resource Utilization Through S.T.E.M Education: A Pathway to Innovative Problem-Solving - Kumar, Amit; Ozma, Ozma (Journal of Neonatal Surgery, 2025)
This study looks at how resources have been availed to 90 students in STEM-oriented Schools of Specialized Excellence (SoSE) in Delhi: affiliated non-STEM schools, and a public school, while trying to figure out the way forward on effective STEM solutions to all kinds of problem-solving. Analysing survey responses according to 30 SoSE, 30 Non-SoSE, and 30 Public School student, the study lines out strong divergent modes of resource utilization for innovation. In fact, non-SoSE students did better than them on 7 out of 10 metrics in spite of limited institutional support available to them. The most gender-discrepant cases within SoSE show that boys expressed 12-27% higher confidence in terms of the efficiency of tools (Q1) as well as using those very same tools (Q3), whereas girls dominated in their ability to reuse past experiences (Q8). Among systemic weak spots was that 28% of SoSE respondents were unable to select resources with Q6: "I use whatever the teacher provides," and 22% found time wasted in group work: Q4: "Group work wastes time." Insights note qualitative contradictions: while students from non-SoSE are outperforming their SoSE counterparts, they are focusing on infrastructure than the building blocks of skills. Girls' adaptive learning strategies (Q8) can convert that potential to iterative innovation, whereas technology-related aspects for boys seem to follow the general tendency of the world. Public school challenges closely resemble conditions in digital India, with only 18.4% functional computer labs across schools (ASER 2022). Bridging these three gaps will be possible through the following pathways: Mobile STEM Labs: Use of shared resources such as 3D printers, coding kits into underserved schools. Gender interventions: Workshops for girls on open sources' tools and boys for collaborative problem solving. Curriculum Reforms: Doing project-based learning instead of examinations, like IoT prototypes and data analysis challenges. In fact, aligning resource allocations with pedagogical innovation is what this study offers pertinent strategies that push forward the goals of transforming STEM education into a catalyst for equitable, real-world problem-solving, as per the prescriptions of India's National Education Policy (NEP) 2020.